Mendudukkan status hukum asuransi syariah dalam tinjauan fuqaha kontemporer - Muhammad Nadratuzzaman Hosen; Deden Misbahuddin Muayyad (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2013)
Insurance Law in The contemporary Islamic Jurists Reviews. The aim of this article is to explain the insurance points of view of contemporary Islamic jurists. In the classical fiqh literatures, discussion of insurance can not be found except in the book of Rad al Muhtar ‘ala Dar al Mukhtar, this book ispublished by Ibn Abidin Hanafiyah as a Islamic Jurist. The Insurance is allowed by the majority of contemporary jurists, namely, insurance ta’awuni based on tabarru (donation), while insurance tijari is not allowed because it contains elements that are prohibited such as riba and gharar.